ANALISIS KAUSALITAS INVESTASI ASING LANGSUNG (FDI), EKSPOR DAN PERTUMBUHAN EKONOMI DI INDONESIA - Radha Ikhwan; Ariusni Ariusni (Universitas Negeri Padang, 2019)
This study examines the causal relationship between foreign direct investment (FDI), exports and economic growth in Indonesia by using Vector Error Corroction Estimates (VECM) time series models during the period 1982 - 2017. The results show that (1)There is no causal relationship between economic growth and investment foreign direct investment (FDI), there is a one-way relationship between foreign direct investment (FDI) and economic growth, where only foreign direct investment (FDI) affects economic growth. (2)There is no causal relationship between economic growth and exports, where there is no influence between the two. (3)There is no causal relationship between foreign direct investment (FDI) and exports, where there is a one-way relationship between foreign direct investment (FDI) and exports, where only foreign direct investment (FDI) affects exports.